On the convolution and neutrix convolution of the functions $\boldsymbol{\sinh^{-1}x}$ and $\boldsymbol{x^r}$ - Fisher, Brian; Al-Sirehy, Fatma (Sarajevo Journal of Mathematics, 2015)
The neutrix convolution $\sinh^{-1}x \circledast x^r$ is evaluated for $r=0,1,2,… .$ Further results are also given.